Dampak Gaya Belajar dalam Menyelesaikan Soal Matematika Divergen yang Memuat Indikator Kemampuan Representasi Matematis - Saputra, Andari; Dasari, Dadan; Priatna, Nanang (SAP (Susunan Artikel Pendidikan), 2024)
Each student represents mathematical concepts uniquely. Therefore, this study aims to investigate how variations in students' learning styles impact their ability to solve divergent problems that measure their capacity in mathematical representation. This study utilized a one-way ANOVA test and quantitative methodology. A total of 23 eighth-grade students from one of the junior high schools in Bandung were sampled. They were selected on Tuesday, April 30, 2024, from 94 eighth-grade students using a simple random sampling technique. Learning style questionnaires and mathematical representation ability tests with divergent geometry and linear equation problems were used to collect data. The results showed that learning style, at the 5% significance level, affected symbolic mathematical representation ability yet it did not affect verbal or visual mathematical representation ability. Students with visual learning styles performed best when answering problems using symbolic mathematical representation ability, based on further investigation using post hoc tests.